Expert Validation of Ethnoscience-Based Teaching Materials to Develop Student Competence in Critical Thinking and Caring Attitudes - Hikmawati Hikmawati; I Wayan Suastra; Ketut Suma; A A Istri Agung Rai Sudiatmika (Universitas Hamzanwadi, 2024)
The aim of this research is to describe the results of expert validation of ethnoscience-based teaching materials to develop student competence in critical thinking and caring attitudes. Expert validation in this research is part of the development of ethnoscience-based teaching materials to develop student competence in critical thinking and caring attitudes using the 4D model. This model includes stages, namely Define, Design, Develop, Disseminate so that it will produce ethnoscience-based teaching materials that are valid, practical and effective in developing students' competence in critical thinking and caring attitudes. Expert validation is included in the Develop stage. Validation of ethnoscience-based teaching materials to develop students' competence in critical thinking and caring attitudes was carried out by 3 experts, namely material experts, media experts and language experts. The research results show that the assessment from material experts is 96.7, media experts are 90.5, and language experts are 100. Thus, the average value of expert validation assessments is 95.7, including the Very Valid criteria. The product, in the form of ethnoscience-based teaching materials to develop students' competence in critical thinking and caring attitudes, was revised based on input from validators. The results of product revisions before and after validation are divided into 5 things, namely: 1) Adding indicators and numbering to Basic Competencies; 2) Improvements to tables that were previously scanned from source or reference books were revised by creating tables manually. The table has also been assigned a sequential number; 3) Addition of photos and videos related to ethnoscience; 4) Ethnoscience-based investigative activities; 5) Changes in the appearance and form of the formative tests available at the end of each chapter.